Fiji Investment Approvals Reform Program : A Donor Update Document - International Finance Corporation; World Bank (World Bank, Washington, DC, 2013)
The investment approvals reform program Fiji started in September 2004 for an initial 12 month period in association with the Ministry of Commerce, Business Development and Investment (MCBDI) and with the support of the Ministry of Finance and National Planning (MFNP). Details on how the program was developed and its stages are set out in the Appendix. The program incorporates the provision of hands-on, practical assistance to the 18 government agencies involved in implementing reforms to their investment approval procedures. The key objectives are to: Facilitate improved efficiencies within the relevant government agencies through a change management process that will result in a sustainable and long term improvement in investment approval processing procedures; provide specialist advice and assistance to government agencies identified as having priority in reforming/streamlining their approval procedures; establish workable procedures for effective coordination between the various government agencies involved in investment approvals, ensure that each government agency can effectively monitor their performance through self-assessment processes and that procedures are in place to rectify shortcomings in achieving realistic targets on a sustainable basis and set in place constructive dialogue between government and the private sector to ensure that the reform process in maintained and expanded to a mutually agreed agenda.